The relationship between job stressors and mood states among field supervisors at WKB Plantation, Miri - Yong, Ling (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to identify the relationship between job stressors and mood states among field supervisors. Job stressors and mood states offield supervisors received limited research attention Correlational design and cluster sampling was used in this study. Data from 136 field supervisors working for WKB Plantation were collected The result of the study indicated that weak relationship between job stressors and mood states among field supervisors in studied plantation Respondents agree that role ambiguity, co-worker support and conflict at work were related to their mood states. Between the entire job stressors that was selected from the National Institute for Occupational Safety and Health Generic Job Stress Questionnaire (NGJSQ),role ambiguity is the dominant factor that influence mood states of field supervisors. Furthermore, the theoretical and practical implications of the findings were discussed in detail and directions for future research were identified